Self-reports of well-being: Are they valid even if we can’t remember everything that happens to us? - TOV, William (Institutional Knowledge at Singapore Management University, 2014)
People can complete self-report measures of happiness and satisfaction fairly quickly. This suggests that they are not recalling every event they have experienced during a specific period of time. Previous researchers have thus argued that well-being judgments are made-up on the spot from whichever events happen to be on the person’s mind. I report the results of two studies that measured people’s experiences over a period of three-weeks (Study 1) or two months (Study 2). I evaluate the extent to which our conscious recollection of specific events trumps our actual experiences and conclude that people may be able to (1) summarize their experiences fairly comprehensively; (2) these summaries are based on their actual experiences and are distinct from their conscious memory of specific events; and (3) self-reported well-being is more strongly predicted by summarized experiences than conscious recollection of a few events.